The present state of Old Testament studies in the Low Countries : a collection of Old Testament studies published on the occasion of the seventy-fifth anniversary of the Oudtestamentisch Werkgezelschap - Spronk, Klaas. (Oudtestamentische Studiën, Old Testament Studies, 2016)
In The Present State of Old Testament Studies in the Low Countries fifteen leading scholars from Belgium and the Netherlands give an overview of their work. This collection celebrating the seventy-fifth anniversary of the Oudtestamentisch Werkgezelschap brings together the results of high quality research on many fields, from computer-assisted analysis to biblical theology, from the archaeology of Palestine to early rabbinic exegesis, from logotechnical analysis to delimitation criticism. It shows that Old Testament research in Belgium and the Netherlands is multifaceted and innovative.